2007
DOI: 10.1186/1471-2180-7-57
|View full text |Cite
|
Sign up to set email alerts
|

Brucella suis urease encoded by ure 1 but not ure 2 is necessary for intestinal infection of BALB/c mice

Abstract: Background: In prokaryotes, the ureases are multi-subunit, nickel-containing enzymes that catalyze the hydrolysis of urea to carbon dioxide and ammonia. The Brucella genomes contain two urease operons designated as ure1 and ure2. We investigated the role of the two Brucella suis urease operons on the infection, intracellular persistence, growth, and resistance to low-pH killing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 39 publications
2
54
0
1
Order By: Relevance
“…2). Our data strongly suggest that urease, which has been reported to be related to resistance to gastrointestinal stress in several bacteria in the presence of urea (Bandara et al, 2007;Maroncle et al, 2006), is regulated by OmpR during acid survival in YpIII. Studies with other bacterial species have shown that urease expression is activated by H-NS, UreR, NikR and ArsR (Coker et al, 2000;Dattelbaum et al, 2003;Delany et al, 2005;Pflock et al, 2005;Pflock et al, 2006a), but to our knowledge OmpR-mediated urease expression has not been reported previously.…”
Section: Discussionsupporting
confidence: 69%
“…2). Our data strongly suggest that urease, which has been reported to be related to resistance to gastrointestinal stress in several bacteria in the presence of urea (Bandara et al, 2007;Maroncle et al, 2006), is regulated by OmpR during acid survival in YpIII. Studies with other bacterial species have shown that urease expression is activated by H-NS, UreR, NikR and ArsR (Coker et al, 2000;Dattelbaum et al, 2003;Delany et al, 2005;Pflock et al, 2005;Pflock et al, 2006a), but to our knowledge OmpR-mediated urease expression has not been reported previously.…”
Section: Discussionsupporting
confidence: 69%
“…melitensis wild type strain 16M, B. suis wild type 1330, and the urease-deficient B. suis mutant 1330Δure1K [6] were obtained from our bacterial culture collection. The attenuated ctpA mutant of B. suis (1330ΔctpA) [7] was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were grown in 25 mL TSB at 37˚C with shaking at 180 rpm, and Klett units were recorded every three hours using a Klett-Summerson colorimeter. The specific activity of urease was determined using the extracts prepared from the strains grown in TSB and harvested during logarithmic growth, as described elsewhere [6,9].…”
Section: Methodsmentioning
confidence: 99%
“…In order for proper assembly of the urease metallocenter, all four of the accessory proteins must be functional. Although urease has been demonstrated to be an important virulence factor in a number of bacteria, such as Helicobacter pylori (11), Yersinia enterocolitica (10), Proteus mirabilis (9), Brucella species (1,45), and Klebsiella pneumoniae (27), the role of urease in EHEC pathogenesis is not defined. It is possible that, like some other bacteria, EHEC exploits the enzyme urease as an additional factor to aid with surviving the low pH conditions as it passes through the stomach.…”
mentioning
confidence: 99%